Work and Play During Covid-19 - Joe Jones; Jon Winder (Janeway JS, 2021)
The global pandemic and resultant lockdowns are challenging our traditional assumptions about the times and spaces of labour and leisure - but how were these norms established and why have they had such an enduring appeal? In this paper, we take a long view to investigate the philosophical and historical roots of the binary distinction between work and play and outline ways in which these long-held ideas are being increasingly challenged. As lockdown measures are relaxed, we urgently need to develop more nuanced conceptions of the spatial and temporal conditions of work and leisure to ensure a more equitable and compassionate post-lockdown world.